Exploring Kartini’s Thought: Inspiring Social Change in the Colonial Era - Khonifiyah, Shofi Lailatul; Rachmadani, Syahira Septi; Firmansyah, Ananda Zulham (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study aims to explore the ideas of Raden Ajeng Kartini and analyze how her thoughts inspired social change during the Dutch colonial era in the Dutch East Indies. Through literature review and analysis of Kartini’s letters and relevant literature, the research seeks to examine her responses to the social, political, and cultural conditions that discriminated against indigenous people, especially women, during colonial times. Key aspects of Kartini’s thought highlighted in this study include her critique of seclusion traditions and forced marriages, the importance of education for women, ideas of gender equality, and her vision for national progress. The research also traces the influence of Kartini’s ideas on the women’s emancipation movement and the development of education in Indonesia during the national awakening period. Findings reveal that Kartini actively criticized the patriarchal culture that restricted women’s roles, including the practice of female seclusion that limited their freedom in areas such as education, social life, and the economy. She worked to expand access to education for women and promoted gender equality through the establishment of women’s schools. Thus, Kartini’s struggle for gender equality and national advancement continues to have a significant impact to this day.